2021
DOI: 10.1038/s41598-021-85584-w
|View full text |Cite
|
Sign up to set email alerts
|

Salvadora persica mediated synthesis of silver nanoparticles and their antimicrobial efficacy

Abstract: Silver nanoparticles (AgNPs) exhibit strong antimicrobial properties against many pathogens. Traditionally employed chemical methods for AgNPs synthesis are toxic for the environment. Here, we report a quicker, simpler, and environmentally benign process to synthesize AgNPs by using an aqueous ‘root extract’ of Salvadora persica (Sp) plant as a reducing agent. The synthesized Salvadora persica nano particles (SpNPs) showed significantly higher antimicrobial efficacy compared to earlier reported studies. We cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Other recent study by root extract of Salvadora persica mediated silver nanparticles, also reveals that ZOI will also depend upon the size of the nanoparticles and concentration of nanoparticles. Smaller the size of nanoparticles more easily the nanoparticles will percolate through the cell membrane and induce toxicity and cause cell death in both gram positive Staphylococcus epidermidis and gram negative Escherichia coli bacteria 42 . In the past Kim et al and Feng et alalso studied the antibacterial efficacy of silver nanocomposite hydrogels and mechanistic effect of AgNPs against Escherichia coli and Staphylococcus aureus also reveals similar results in which protein synthesis is arrested due AgNPs 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Other recent study by root extract of Salvadora persica mediated silver nanparticles, also reveals that ZOI will also depend upon the size of the nanoparticles and concentration of nanoparticles. Smaller the size of nanoparticles more easily the nanoparticles will percolate through the cell membrane and induce toxicity and cause cell death in both gram positive Staphylococcus epidermidis and gram negative Escherichia coli bacteria 42 . In the past Kim et al and Feng et alalso studied the antibacterial efficacy of silver nanocomposite hydrogels and mechanistic effect of AgNPs against Escherichia coli and Staphylococcus aureus also reveals similar results in which protein synthesis is arrested due AgNPs 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…In another report, spherical silver nanoparticles with average size of 20.49 nm were prepared by utilizing Duchesnea indica and tested toward E. coli (MIC = 0.53 mg/mL), S. typhi (MIC = 0.01 mg/mL), A. alternata (MIC = 0.51 mg/mL), and M. canis (MIC = 0.53 mg/mL) [233]. Arshad, Hammad, et al reported a simpler, quicker, and ecofriendly approach to prepare silver nanoparticles by utilizing Salvadora persica aqueous root extract and tested them toward S. epidermidis ATCC12228 (MIC = 0.39 µg/mL) and E. coli (MIC = 0.19 µg/mL) [234]. In another report, Tripathi, Deepika, et al examined the cytotoxic efficiency of Asparagus officinalis-mediated silver nanoparticles toward a cervical cancer cell line (SiHa) [235].…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 99%
“…Numerous investigations have described the antimicrobic effect of SP on various types of bacteria [ 8 , 106 , 107 ]. SP extracts and products have been shown to have significant bactericidal activity against Gram-positive and Gram-negative bacteria, as well as suppressing bacterial biofilms, in a number of studies, reassuring the use of SP as an antimicrobial drug in a variety of diseases [ 8 , 108 , 109 ].…”
Section: Modes Of Action Of Salvadora Persica As Potential Adjuncts During Periodontal Therapy and In Periodontitis-asmentioning
confidence: 99%